Russian colonization of Alaska, Baranov's era, 1799-1818 - Grinëv, A. V. (Andreĭ Valʹterovich) (Russian colonization of Alaska, 2020)
"This first thorough examination of the origin and evolution of the Russian state and the subsequent colonization of Siberia and North America by Russians focuses on the politarist social and economic strategies that distinguished Russian colonization of Alaska from similar processes occurring in the New World under the aegis of other European powers except Spain."--